Liquid crystal alignment agent, liquid crystal alignment film using the same, and liquid crystal display element
By using liquid crystal alignment agents of polyamic acid and polyimide with specific structures and silanization treatment, the problem of liquid crystal display components between high precision and low cost is solved, and high voltage retention and low cost are achieved. A liquid crystal alignment film of cost.
Patent Information
- Application Number
- CN202080011288.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-31
- Filing Date
- 2020-01-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-01-29
AI Technical Summary
The existing liquid crystal display elements are difficult to take into account both high precision and low cost, especially in realizing high reliability of liquid crystal orientation films.
The liquid crystal alignment agent of polyamic acid and polyimide having a specific structure is adopted. The liquid crystal alignment agent is imidized by introducing a trialkyl silyl structure and imidizing it with a silanizing agent to form a high molecular weight polyimide. amine precursor, thereby improving the reliability of the liquid crystal orientation film.
It is achieved that even with polyamic acid, it has the same reliability as or above as soluble polyimide, and it has excellent performance in high voltage retention rates, reducing manufacturing costs.
Smart Images

Figure FDA0005185049450000011 
Figure FDA0005185049450000012 
Figure FDA0005185049450000013
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal aligning agent for producing a liquid crystal display element, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element using the liquid crystal aligning film. Background Art
[0002] Liquid crystal display elements are known as lightweight, thin, and low-power display devices.
[0003] The liquid crystal display element is composed of a pair of transparent substrates with electrodes sandwiching a liquid crystal layer. A liquid crystal alignment film for controlling the arrangement state of the liquid crystal is usually provided on the surface of the substrate in contact with the liquid crystal. As the liquid crystal alignment film, a polyimide-based liquid crystal alignment film is mainly used, which is formed by applying a liquid crystal alignment agent with a polyimide precursor such as polyamic acid (also called polyamide-based acid) or a solution of a soluble polyimide as the main component to a substrate, etc. and sintering it.
[0004] As liquid crystal display elements become increasingly refined, in view of the requirements for suppressing the reduction in contrast of liquid crystal display elements and reducing afterimages, for liquid crystal alignment films, in addition to excellent liquid crystal orientation and stable pretilt angle performance, high voltage holding rate, suppression of afterimages caused by AC drive, and low residual charge when DC voltage is applied are also important.
[0005] As a polyimide-based liquid crystal alignment film, in order to meet such requirements, a technology for modifying the ends of polyamic acid and polyimide using various structures has been proposed. For example, in order to achieve improved liquid crystal orientation, high pretilt angle, short afterimage elimination time and high reliability, an imidized polymer with modified ends by reacting with a monoanhydride, a monoamine compound and a monoisocyanate compound has been proposed (see Patent Document 1).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2001-296525 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, in recent years, high-definition liquid crystal display elements for mobile phones and tablet terminals, whose market share has been rapidly expanding, are required to have further improved characteristics, and in particular, to achieve high reliability at low cost.
[0011] In order to obtain high reliability, a liquid crystal alignment agent using a soluble polyimide is generally used, but the manufacture of the soluble polyimide requires the polyamic acid to be deteriorated, and the cost is higher than that of the manufacture of the polyamic acid. However, the liquid crystal alignment film using the polyamic acid has the disadvantage of lacking the reliability of the film compared to the liquid crystal alignment film using the soluble polyimide.
[0012] A main object of the present invention is to provide a liquid crystal aligning agent having reliability equal to or higher than that of a soluble polyimide, specifically, having high voltage holding ratio characteristics, even when a polyamic acid is used.
[0013] Solutions for solving problems
[0014] The present inventors have conducted intensive studies to solve the above problems and have completed the present invention. That is, the gist of the present invention is as follows.
[0015] 1. A liquid crystal aligning agent comprising at least one selected from a polyamic acid and a polyimide having a structure represented by the following formula (1).
[0016] -COOR1 (1)
[0017] In the formula, R1 represents a trialkylsilyl group.
[0018] Effects of the Invention
[0019] By using the liquid crystal aligning agent of the present invention, it is not necessary to use a complex manufacturing process such as polyamic acid ester and soluble polyimide, and a liquid crystal aligning agent having a reliability equal to or higher than that of soluble polyimide, specifically having a high voltage holding rate characteristic, can be obtained even if polyamic acid is used. It should be noted that even if the present invention is applied to soluble polyimide, the same effect can be obtained. DETAILED DESCRIPTION
[0020] The liquid crystal aligning agent of this invention contains at least one kind of polyamic acid which has the structure of following formula (1) and the polyimide which is an imide product thereof.
[0021] -COOR1 (1)
[0022] In the formula, R1 represents a trialkylsilyl group. Specific examples include the structures of the following formulae (1-1) to (1-4). * represents a bonding bond. More preferably, it is a tert-butylsilyl group.
[0023]
[0024] In order to introduce such a structure into the polyimide, a method of using a silanization agent during and after the polymerization of the polyimide precursor is used. The silanization agent used in the present invention can be a commercially available silanization agent as long as it can introduce a trialkylsilyl group, and preferably a compound selected from the following formulas (S-1) to (S-5) is used. More preferably, (S-1) and (S-2) are used.
[0025]
[0026] <Tetracarboxylic acid derivatives>
[0027] The polyimide contained in the liquid crystal aligning agent of the present invention is obtained by imidizing a polyimide precursor obtained by a reaction between a tetracarboxylic acid derivative and a diamine. Specific examples of the materials used and the production method are described in detail below.
[0028] As the tetracarboxylic acid derivative used for producing the polyimide precursor, not only tetracarboxylic dianhydride but also tetracarboxylic acid, a tetracarboxylic acid dihalide compound, a tetracarboxylic acid dialkyl ester, and a tetracarboxylic acid dialkyl ester dihalide which are derivatives thereof can be mentioned.
[0029] As the tetracarboxylic dianhydride or its derivative, the tetracarboxylic dianhydride or its derivative represented by the following formula (3) is particularly preferred.
[0030]
[0031] In formula (3), the structure of X1 is not particularly limited as long as it is a tetravalent organic group. As preferred specific examples, the following formulas (X1-1) to (X1-44) can be cited. From the viewpoint of liquid crystal orientation, X1 is preferably (X1-1) to (X1-3), (X1-5), (X1-7) to (X1-10), (X1-18), (X1-24), (X1-27) to (X1-43).
[0032]
[0033]
[0034] In formulas (X1-1) to (X1-4), R3 to R 23 Each of R3 to R4 is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms and containing a fluorine atom, or a phenyl group. 23 A hydrogen atom, a halogen atom, a methyl group or an ethyl group is preferred, and a hydrogen atom or a methyl group is more preferred.
[0035] Specific examples of the formula (X1-1) include the following formulas (X1-1-1) to (X1-1-6). (X1-1-1) is particularly preferred from the viewpoint of liquid crystal orientation.
[0036]
[0037] <Diamine>
[0038] The diamine used for producing the polyimide precursor is represented by the following formula (2).
[0039]
[0040] In the above formula (2), A1 and A2 are each independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an alkynyl group having 2 to 5 carbon atoms.
[0041] The structure of Y1 is not particularly limited, but preferred structures include the following (Y-1) to (Y-177).
[0042]
[0043]
[0044]
[0045]
[0046]
[0047]
[0048] In the above formula, Me represents a methyl group, R 1 It represents a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms.
[0049]
[0050] Among them, as the structure of Y1, (Y-7), (Y-8), (Y-16), (Y-17), (Y-18), (Y-20), (Y-21), (Y-22), (Y-27 ), (Y-28), (Y-29), (Y-35), (Y-37), (Y-38), (Y-43), (Y-48), (Y-53) ~ (Y-56), (Y-61), (Y-64)~(Y-66), (Y-69), (Y-71), (Y-72), (Y-76), (Y-77), (Y-80), (Y-81), (Y-82), (Y -83), (Y-156), (Y-159), (Y-160), (Y-161), (Y-162), (Y-168), (Y-169), (Y-170), (Y-1 71), (Y-173), (Y-175), (Y-178) to (Y-182), especially (Y-7), (Y-8), (Y-16), (Y-17), (Y-18) , (Y-21), (Y-22), (Y-27), (Y-28), (Y-29), (Y-37), (Y-38), (Y-53) ~ (Y-56), (Y-61), ( Y-64)~(Y-66), (Y-69), (Y-72), (Y-76), (Y-81), (Y-156), (Y-159), (Y-160), (Y-161) , (Y-162), (Y-168), (Y-169), (Y-170), (Y-171), (Y-173), (Y-175), (Y-178)~(Y-182).
[0051] <Production of polyimide precursor - polyamic acid>
[0052] The polyamic acid as a polyimide precursor used in the present invention can be produced by the following method.
[0053] Specifically, it can be synthesized by reacting tetracarboxylic dianhydride and diamine in the presence of a solvent at -20 to 150°C, preferably 0 to 50°C, for 30 minutes to 24 hours, preferably 1 to 12 hours.
[0054] The reaction of the diamine component and the tetracarboxylic acid component is usually carried out in a solvent. The solvent used at this time is not particularly limited as long as it dissolves the generated polyimide precursor. Specific examples of the solvent used in the reaction are listed below, but are not limited to these examples. For example, it can be listed: N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or 1,3-dimethyl-imidazolidinone.
[0055] When the polyimide precursor has high solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or a solvent represented by the following formula [D-1] to [D-3] can be used.
[0056]
[0057] In formula [D-1], D 1 represents an alkyl group having 1 to 3 carbon atoms, wherein D 2 represents an alkyl group having 1 to 3 carbon atoms, wherein D 3 It represents an alkyl group having 1 to 4 carbon atoms.
[0058] These solvents can be used alone or in combination. Moreover, even if it is a solvent that does not dissolve the polyimide precursor, it can be mixed with the solvent in the range that the generated polyimide precursor does not precipitate and used. In addition, the moisture in the solvent hinders the polymerization reaction, further becoming the reason for hydrolyzing the generated polyimide precursor, so the solvent is preferably used a dehydrated solvent.
[0059] The concentration of the polyamic acid polymer in the reaction system is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, from the viewpoint of preventing the polymer from precipitating and easily obtaining a high molecular weight product.
[0060] When the silanizing agent is introduced during and after the polymerization of the polyimide precursor, the amount of the introduced agent is preferably 25 to 100 mol%, particularly preferably 75 to 100 mol%, relative to the amount of carboxylic acid in the polyimide precursor. After the silanizing agent is introduced, the polyimide precursor is silylated by stirring at 5° C. to 60° C., preferably 40° C. to 80° C., for 1 to 30 hours, preferably 6 to 24 hours.
[0061] During the reaction, in order to prevent oxidation of the diamine portion in the polyamic acid, it is preferred to replace the system with nitrogen. Furthermore, in order not to change the temperature in the system, it is preferred to provide a reflux device.
[0062] The polyamic acid obtained as described above is injected into the following poor solvent while fully stirring the reaction solution, so that the polymer can be precipitated and recovered. In addition, by repeatedly precipitating, after cleaning with a poor solvent, normal temperature or heat drying can be performed to obtain a powder of purified polyamic acid. The poor solvent is not particularly limited, and water, methanol, ethanol, hexane, butyl cellosolve, acetone, toluene, etc. can be listed.
[0063] <Polyimide>
[0064] The polyimide used in the present invention can be produced by imidizing the polyamic acid or polyamic acid ester.
[0065] Moreover, it can also manufacture by imidizing the polyamic acid which is not silylated by the method mentioned later, dissolving the separated imidized polymer in a solvent, and introducing a silylation agent at the time of manufacturing a liquid crystal aligning agent.
[0066] When polyimide is produced from polyamic acid, chemical imidization in which a catalyst is added to a solution of the polyamic acid obtained by the reaction of a diamine component and tetracarboxylic dianhydride is simple. Chemical imidization is preferred because the imidization reaction is carried out at a relatively low temperature and the molecular weight of the polymer is not easily reduced during the imidization process.
[0067] Chemical imidization can be carried out by stirring the polyamic acid to be imidized in a solvent in the presence of a basic catalyst and an acid anhydride. As a solvent, the solvent used during the above-mentioned polymerization reaction can be used. As a basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be listed. Among them, pyridine has a moderate alkalinity for reacting, so it is preferred. In addition, as anhydrides, acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. can be listed, wherein, if acetic anhydride is used, the purification after the reaction ends becomes easy, so it is preferred.
[0068] The temperature during the imidization reaction is -20 to 140°C, preferably 0 to 100°C, and the reaction time is 1 to 100 hours, preferably 1 to 5 hours.
[0069] The amount of the basic catalyst is 0.5 to 30 times, preferably 2 to 20 times, the amount of the acid anhydride is 1 to 50 times, preferably 3 to 30 times, the amount of the amic acid group. The imidization rate of the obtained polymer can be controlled by adjusting the amount of catalyst, temperature, reaction time, etc.
[0070] When polyimide is produced from polyamic acid ester, chemical imidization in which a basic catalyst is added to the polyamic acid ester solution or a polyamic acid solution obtained by dissolving polyamic acid ester resin powder in a solvent is simple. Chemical imidization is preferred because the imidization reaction proceeds at a relatively low temperature and the molecular weight of the polymer is less likely to decrease during the imidization process.
[0071] Chemical imidization can be carried out by stirring the polyamic acid ester to be imidized in a solvent in the presence of a basic catalyst. As a solvent, the solvent used during the above-mentioned polymerization reaction can be used. As a basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be listed. Among them, triethylamine has sufficient alkalinity for reacting, so it is preferred.
[0072] The temperature during the imidization reaction is -20 to 140°C, preferably 0 to 100°C, and the reaction time is 1 to 100 hours, preferably 1 to 5 hours.
[0073] The amount of the basic catalyst is 0.5 to 30 times by mole, preferably 2 to 20 times by mole, based on the amount of the amic acid ester group.
[0074] The imidization rate of the obtained polymer can be controlled by adjusting the amount of catalyst, temperature, reaction time, etc.
[0075] Since the added catalyst and the like remain in the solution after the imidization reaction, it is preferred to recover the obtained imidization polymer by the method described below and redissolve it in a solvent to obtain the liquid crystal aligning agent of the present invention.
[0076] In addition, in the imidization reaction of polyamic acid or polyamic acid ester, an imidization accelerator can be used. Although the specific example of the imidization accelerator is shown below, it is not limited to these.
[0077]
[0078] D in the above formulas (B-1) to (B-17) is independently a tert-butoxycarbonyl group or a 9-fluorenylmethoxycarbonyl group. The multiple Ds present in formulas (B-14) to (B-17) may be the same as or different from each other. The higher the alkalinity after deprotection by heating, the further the imidization promoting effect of polyamic acid ester and polyamic acid is improved. Therefore, from the perspective of further improving the thermal imidization promoting effect, (B-14) to (B-17) are preferred, and (B-17) is particularly preferred.
[0079] Since the added catalyst etc. remain in the solution after the imidization reaction of a polyamic acid or a polyamic acid ester, it is preferable to recover the obtained imidized polymer by the method described below, and to redissolve it with a solvent to make it the liquid crystal aligning agent of this invention.
[0080] The polymer can be precipitated by injecting the polyimide solution obtained as described above into the following poor solvent while sufficiently stirring. The precipitation is performed multiple times, and after washing with a poor solvent, it is dried at room temperature or by heating to obtain a powder of a purified polyamic acid ester.
[0081] The poor solvent is not particularly limited, and examples thereof include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, and benzene.
[0082] When the obtained polyimide powder is dissolved in a solvent, the solvent (also called a good solvent) is not particularly limited as long as it is a solvent that uniformly dissolves the polymer of the specific structure. For example, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, or 4-hydroxy-4-methyl-2-pentanone can be listed.
[0083] Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, or γ-butyrolactone is preferably used.
[0084] The temperature during the redissolution is preferably 5° C. to 80° C., and more preferably 20° C. to 50° C. The stirring time for the redissolution is preferably 30 minutes to 50 hours, and more preferably 3 hours to 12 hours.
[0085] When the unsilanized polyimide powder is redissolved, a silanized polyimide solution can be obtained by introducing a silanizing agent during stirring during the redissolution. After the silanizing agent is introduced, the silanized polyimide solution can be obtained by stirring at 5° C. to 60° C., preferably 40° C. to 80° C. for 1 to 30 hours, preferably 6 to 24 hours.
[0086] <Liquid crystal alignment agent>
[0087] The liquid crystal aligning agent used in the present invention has a solution form in which at least one selected from the group consisting of polyamic acid and polyimide having the structure of the above formula (1) is dissolved in a solvent.
[0088] The molecular weight of the specific structural polymer is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000, and the number average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and further preferably 5,000 to 50,000.
[0089] The concentration of the polymer in the liquid crystal aligning agent of the present invention can be appropriately changed according to the setting of the thickness of the coating film to be formed, but is preferably 1% by mass or more from the perspective of forming a uniform and defect-free coating film, and is preferably 10% by mass or less from the perspective of the storage stability of the solution. It is particularly preferably 3 to 6.5% by mass.
[0090] The solvent (also referred to as a good solvent) contained in the liquid crystal aligning agent of the present invention will not be particularly limited as long as it is a solvent that uniformly dissolves the specific structure polymer.
[0091] For example, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, or 4-hydroxy-4-methyl-2-pentanone may be mentioned.
[0092] Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, or γ-butyrolactone is preferably used.
[0093] Furthermore, when the solubility of the polymer of the present invention in a solvent is high, it is preferable to use the solvent represented by the above formula [D-1] to formula [D-3].
[0094] The good solvent in the liquid crystal aligning agent of the present invention is preferably 20 to 99% by mass of the entire solvent contained in the liquid crystal aligning agent. Among them, it is preferably 20 to 90% by mass. More preferably, it is 30 to 80% by mass.
[0095] The liquid crystal aligning agent of the present invention may use a solvent (also referred to as a poor solvent) that improves the coating properties and surface smoothness of the liquid crystal aligning film when the liquid crystal aligning agent is applied, as long as the effects of the present invention are not impaired. Specific examples of the poor solvent are given below, but are not limited to these examples.
[0096] For example, ethanol, isopropanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentanol, tert-pentanol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,2-diol, 1,3-diol ... 3-Butanediol, 1,4-Butanediol, 2,3-Butanediol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, dipropyl ether, dibutyl ether, dihexyl ether, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, ethylene glycol monoacetate, ethyl Glycol diacetate, propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, ethylene glycol monobutyl ether, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, propylene glycol monobutyl ether, 1-(butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, and the solvents represented by the formula [D-1] to [D-3] above.
[0097] Among them, 1-hexanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, propylene glycol monobutyl ether, ethylene glycol monobutyl ether or dipropylene glycol dimethyl ether is preferably used.
[0098] The poor solvent is preferably 1 to 80% by mass of the whole solvent contained in the liquid crystal aligning agent, more preferably 10 to 80% by mass, and more preferably 20 to 70% by mass.
[0099] In the liquid crystal aligning agent of the present invention, in addition to the above, as long as the effect of the present invention is not impaired, a polymer other than the polymer described in the present invention, a dielectric or conductive material for the purpose of changing the electrical properties such as the dielectric constant and conductivity of the liquid crystal alignment film, a silane coupling agent for the purpose of improving the adhesion between the liquid crystal alignment film and the substrate, a cross-linking compound for the purpose of improving the hardness and density of the film when the liquid crystal alignment film is made, and an imidization accelerator for the purpose of efficiently performing imidization by heating the polyimide precursor when the coating is fired, etc. can also be added.
[0100] <Liquid crystal alignment film>
[0101] <Liquid crystal display device>
[0102] The liquid crystal alignment film of the present invention can be used for a liquid crystal alignment film of a horizontal orientation type or a vertical orientation type, and is particularly suitable for a liquid crystal alignment film of a liquid crystal display element of a vertical orientation type such as a VA mode or a PSA mode. As a formation method of the liquid crystal alignment film of the present invention, the above-mentioned liquid crystal alignment agent is first applied to a substrate, dried, and fired to obtain a coating film. As a substrate for applying the liquid crystal alignment agent of the present invention, as long as it is a substrate with high transparency, there is no particular limitation, and plastic substrates such as a glass substrate, a silicon nitride substrate, an acrylic substrate, and a polycarbonate substrate can be used. Moreover, from the perspective of process simplification, it is preferred to use a substrate formed with an ITO electrode for liquid crystal drive, etc. In addition, for a reflective liquid crystal display element, if it is only a substrate on one side, an opaque substrate such as a silicon wafer can also be used, and the electrode in this case can also use a material for light reflection such as aluminum.
[0103] As the coating method of the liquid crystal alignment agent of the present invention, spin coating, printing, inkjet and the like can be cited. The drying and firing steps after the liquid crystal alignment agent of the present invention is applied can select any temperature and time. Usually, in order to fully remove the contained solvent, it is dried at 50 to 120°C, preferably at 60 to 100°C for 1 to 10 minutes, preferably for 2 to 5 minutes, and then fired at 150 to 300°C, preferably at 200 to 240°C for 5 to 120 minutes, preferably for 10 to 30 minutes. The thickness of the coating after firing is not particularly limited. If the thickness of the coating after firing is too thin, the reliability of the liquid crystal display element is sometimes reduced. Therefore, the thickness is 5 to 300 nm, preferably 10 to 200 nm.
[0104] The coating film formed as described above may be used as a liquid crystal alignment film as it is, or the coating film may be subjected to an alignment treatment. Examples of the method for performing the alignment treatment include a rubbing method and a photo-alignment treatment method.
[0105] The friction treatment can be performed using an existing friction device. The material of the friction cloth at this time includes cotton, nylon, rayon, etc. The conditions for the friction treatment are usually a rotation speed of 300 to 2000 rpm, a transmission speed of 5 to 100 mm / s, and a press amount of 0.1 to 1.0 mm. Then, ultrasonic cleaning is performed using pure water, alcohol, etc. to remove the residue generated by friction.
[0106] In the photo-alignment treatment, as the radiation irradiated to the coating film, ultraviolet rays and visible light with a wavelength of, for example, 150 to 800 nm can be used. In the case where the radiation is polarized light, it can be linearly polarized light or partially polarized light. In addition, in the case where the radiation used is linearly polarized light or partially polarized light, the irradiation can be performed from a direction perpendicular to the substrate surface, from an oblique direction, or a combination thereof. In the case of irradiating non-polarized radiation, the irradiation direction is set to an oblique direction.
[0107] Next, the liquid crystal display element of the present invention can be produced by any of the following methods of a combination of step (1), step (2) and step (4), or a combination of step (3) and step (4).
[0108] (1) Case of VA-type liquid crystal display element
[0109] Prepare two substrates with liquid crystal alignment films formed as described above, and arrange liquid crystal between the two opposing substrates. Specifically, the following two methods can be listed. The first method is a previously known method. First, two substrates are arranged opposite to each other with a gap (cell gap) between them in a manner that each liquid crystal alignment film is opposite to each other. Next, a sealant is used to bond the peripheral portions of the two substrates, and after the liquid crystal composition is injected into the cell gap divided by the substrate surface and the sealant and in contact with the film surface, the injection hole is encapsulated.
[0110] In addition, the second method is a method called ODF (One Drop Fill: liquid crystal drop injection) method. A sealant such as a UV-curable sealant is applied at a predetermined position on one of the two substrates on which a liquid crystal alignment film is formed, and a liquid crystal composition is further dripped at a predetermined plurality of locations on the surface of the liquid crystal alignment film. Then, another substrate is attached in a manner that the liquid crystal alignment film is opposite, and the liquid crystal composition is extended to the entire surface of the substrate and brought into contact with the film surface. Then, the sealant is cured by irradiating the entire surface of the substrate with ultraviolet light. Ideally, regardless of which method is used, after further heating to a temperature at which the liquid crystal composition used becomes an isotropic phase, it is slowly cooled to room temperature, thereby removing the flow orientation during liquid crystal filling.
[0111] (2) Manufacturing of PSA-type liquid crystal display elements
[0112] The method is similar to the above (1) except that the liquid crystal composition containing the polymerizable compound is injected or dropped. Examples of the polymerizable compound include polymerizable compounds represented by the following formulae (M-1) to (M-7).
[0113]
[0114] (3) When a coating film is formed on a substrate using a liquid crystal aligning agent containing a compound having a polymerizable group
[0115] A method for manufacturing a liquid crystal display element can also be adopted in the same manner as in the above (1), followed by the step of irradiating ultraviolet rays described later. According to this method, as in the case of manufacturing the PSA type liquid crystal display element, a liquid crystal display element with excellent response speed can be obtained with a small amount of light irradiation. The compound having a polymerizable group can be a compound having one or more polymerizable unsaturated groups such as acrylate groups and methacrylate groups in the molecule as shown in the formula (M-1) to (M-7), and the content of the compound having a polymerizable group is preferably 0.1 to 30 parts by mass, and more preferably 1 to 20 parts by mass relative to 100 parts by mass of all polymer components. In addition, the polymer used in the polymer composition can have the polymerizable group. As such a polymer, for example, a polymer obtained by using a diamine component in a reaction can be listed, and the diamine component contains a diamine having a photopolymerizable group at the end.
[0116] (4) Ultraviolet irradiation process
[0117] The liquid crystal box is irradiated with light while a voltage is applied between the conductive films of a pair of substrates obtained by (2) or (3) above. The voltage applied here can be, for example, a direct current or alternating current of 5 to 50 V. In addition, as the irradiated light, for example, ultraviolet light and visible light with a wavelength of 150 to 800 nm can be used, preferably ultraviolet light with a wavelength of 300 to 400 nm. As the light source of the irradiated light, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. The irradiation amount of light is preferably 1000 to 200,000 J / m 2 , more preferably 1000 to 100000 J / m 2 .
[0118] Then, a liquid crystal display element can be obtained by attaching a polarizing plate to the outer surface of the liquid crystal box. Examples of the polarizing plate attached to the outer surface of the liquid crystal box include a polarizing film called "H film" that absorbs iodine while stretching polyvinyl alcohol and sandwiched between a cellulose acetate protective film or a polarizing plate composed of the H film itself.
[0119] The liquid crystal display element of the present invention can be effectively applied to various devices, for example, it can be used in various display devices such as watches, portable game consoles, word processors, notebook computers, car navigation systems, camcorders, PDAs (Personal Digital Assistants), digital cameras, mobile phones, smart phones, various monitors, LCD televisions, and information displays.
[0120] Example
[0121] The present invention is described in more detail below by way of examples. However, the present invention is not to be construed as being restrictive by these examples. The abbreviations of the compounds used are shown below.
[0122] (Specific diamine)
[0123] DBA: 3,5-diaminobenzoic acid
[0124] 3AMPDA: 3,5-diamino-N-(pyridin-3-ylmethyl)benzamide
[0125] DA-1: Compound represented by formula [DA-1] (diamine having a specific side chain structure)
[0126]
[0127] (Tetracarboxylic acid component)
[0128] PMDA: Pyromellitic anhydride
[0129] The following compounds represented by [D1] to [D2]
[0130] D1: 1,2,3,4-cyclobutanetetracarboxylic dianhydride
[0131] D2: Bicyclo[3,3,0]octane-2,4,6,8-tetracarboxylic dianhydride
[0132] (Silanizing agent component)
[0133] Compounds represented by the following formulas [S-1] to [S-5] (silylation agents)
[0134]
[0135] (Solvent)
[0136] NMP: N-methyl-2-pyrrolidone
[0137] BCS: Ethylene glycol monobutyl ether
[0138] <Determination of Molecular Weight of Polyimide>
[0139] The molecular weight of the polyimide in the synthesis example was measured as follows using a room temperature gel permeation chromatography (GPC) apparatus (SSC-7200) manufactured by Senshu Scientific Co., Ltd. and columns (KD-803 and KD-805) manufactured by Shodex Corporation.
[0140] Column temperature: 50°C
[0141] Eluent: N, N'-dimethylformamide (as additives, lithium bromide monohydrate (LiBr·H2O) 30mmol / L, anhydrous phosphoric acid (orthophosphoric acid) 30mmol / L, tetrahydrofuran (THF) 10ml / L)
[0142] Flow rate: 1.0ml / min
[0143] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide manufactured by TOSOH (molecular weight of about 9,000,000, 150,000, 100,000, and 30,000) and polyethylene glycol manufactured by Polymer Laboratories (molecular weight of about 12,000, 4,000, and 1,000).
[0144] <Measurement of Imidization Ratio>
[0145] The imidization ratio of the polyimide in the synthesis example was measured as follows. 20 mg of the polyimide powder was added to an NMR sample tube (NMR sample tube standard manufactured by Kusano Scientific Co., Ltd.) ), 0.53 ml of deuterated dimethyl sulfoxide (DMSO-d6, 0.05% TMS mixture) was added to completely dissolve the solution.
[0146] The solution was measured for 500 MHz proton NMR using an NMR measuring instrument (JNW-ECA500) manufactured by DATUM Co., Ltd. of Japan Electronics Co., Ltd. The imidization rate was determined by the following calculation formula using the peak accumulation value of the proton derived from the structure that did not change before and after imidization and the proton peak accumulation value derived from the NH group of the amic acid appearing around 9.5 to 10.0 ppm, which was determined by the proton peak accumulation value derived from the NH group of the amic acid.
[0147] Imidization rate (%) = (1-α·x / y) × 100
[0148] <Synthesis of polyimide polymer>
[0149] <Synthesis example 1>
[0150] In a 100 ml four-necked flask with a stirrer and a nitrogen inlet tube, DBA 2.74 g (18.0 mmol), 3AMPDA 3.27 g (13.5 mmol), and DA-1 5.14 g (13.5 mmol) were weighed and diluted with NMP to a solid content concentration of 20%. After stirring at room temperature for 30 minutes, D2 2.25 g (8.99 mmol) was added, and the mixture was diluted with NMP again to a solid content concentration of 20%, and heated and stirred at 60°C for 1 hour. After the obtained reaction solution was cooled to below 17°C, PMDA 1.96 g (8.99 mmol) was added, and after diluting with NMP to 20%, it was stirred at room temperature for 5 hours. Finally, D1 5.11 g (26.1 mmol) was diluted with NMP to a solid content concentration of 20%, and heated and stirred at 40°C for 6 hours. The obtained polymerization solution was cooled to room temperature, thereby obtaining a polyamic acid polymerization solution (PAA-1).
[0151] <Synthesis example 2>
[0152] NMP (103.85 g) was added to PAA-1 (50.0 g) to dilute to 6.5% by mass, and then acetic anhydride (6.67 g) and pyridine (2.58 g) were added as imidization catalysts, and the mixture was reacted at 70°C for 3 hours. The reaction solution was put into methanol (570.9 g), and the obtained precipitate was filtered. The precipitate was washed with methanol and dried under reduced pressure at 60°C to obtain a polyimide powder (SPI-1) of Synthesis Example 1. The imidization rate of the polyimide was 72%, the number average molecular weight was 11,800, and the weight average molecular weight was 41,800.
[0153] <Synthesis example 3>
[0154] After adding 1.75 g of S-1 to PAA-1 (10.0 g), the mixture was heated and stirred at 50° C. for 12 hours to obtain a polyamic acid silyl ester polymer solution. (PASE-1)
[0155] <Synthesis Example 4-7>
[0156] In Synthesis Example 3, except that S-2 to S-5 in the amounts shown in the following table were added instead of S-1, all the same treatments as in Synthesis Example 3 were performed to obtain polyamic acid silyl ester polymer solutions. (PASE-2 to PASE-5)
[0157] [Table 1]
[0158]
[0159] <Example 1>
[0160] NMP (14.0 g) and BCS (8.0 g) were added to the polyamic acid silyl ester polymer solution (PASE-1) (6.0 g) obtained in Synthesis Example 3, and stirred at 25° C. for 5 hours. Thus, the liquid crystal aligning agent [1] of Example 1 was obtained. No abnormalities such as turbidity and precipitation were found in the liquid crystal aligning agent, and it was confirmed that the resin component was uniformly dissolved.
[0161] <Example 2-5>
[0162] NMP (14.0 g) and BCS (8.0 g) were added to the polyamic acid silyl ester polymer solution (PASE-2 to PASE-5) (6.0 g) obtained in Synthesis Example 4-7, and stirred at 25° C. for 5 hours. Thus, the liquid crystal aligning agent [2-5] of Example 2-5 was obtained. No abnormalities such as turbidity and precipitation were found in the liquid crystal aligning agent, and it was confirmed that the resin component was uniformly dissolved.
[0163] <Comparative Example 1>
[0164] NMP (14.0 g) and BCS (8.0 g) were added to the polyamic acid polymer solution (PAA-1) (6.0 g) obtained in Synthesis Example 1, and stirred at 25° C. for 5 hours. Thus, a liquid crystal aligning agent of Comparative Example 1 was obtained. Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed that the resin component was uniformly dissolved.
[0165] <Production of Liquid Crystal Cell>
[0166] The liquid crystal alignment agent obtained above was spin-coated on the ITO surface of an alkali-free glass substrate with ITO (30 mm in length, 40 mm in width, and 0.7 mm in thickness) that had been cleaned with pure water and IPA (isopropyl alcohol), and then fired on a hot plate at 70°C for 90 seconds and then fired in an infrared heating furnace at 230°C for 20 minutes to produce a polyimide-coated substrate with a film thickness of 100 nm.
[0167] Two polyimide-coated substrates were prepared by the above method. After 4 μm bead spacers were spread on the liquid crystal alignment film surface of one substrate, a thermosetting sealant (XN-1500T manufactured by Kyoritsu Chemical Co., Ltd.) was printed thereon. Next, the surface of the other substrate on which the liquid crystal alignment film was formed was used as the inner side, and after being bonded to the previous substrate, the sealant was cured to produce an empty box. Liquid crystal MLC-3023 (trade name manufactured by MERCK Co., Ltd.) containing a polymerizable compound for PSA was injected into the empty box by the reduced pressure injection method to produce a liquid crystal box. The voltage holding ratio of the liquid crystal box was measured.
[0168] Next, while applying a DC voltage of 15 V to the liquid crystal cell, a 7 J / cm 2 The UV (also referred to as the primary PSA treatment) was passed through a 325 nm cutoff filter. The UV illuminance was measured using UV-MO3A manufactured by ORC Corporation.
[0169] Then, in order to deactivate the unreacted polymerizable compound remaining in the liquid crystal cell, UV (UV lamp: FLR40SUV32 / A-1) was irradiated for 30 minutes using a UV-FL irradiation device manufactured by Toshiba Lighting & Technology Co., Ltd. without applying voltage (also referred to as secondary PSA treatment). Then, the voltage holding ratio was measured.
[0170] <Evaluation of voltage holding ratio>
[0171] The liquid crystal cell prepared above was used to apply a voltage of 1V for 60μs in a hot air circulation oven at 60°C. The voltage was measured after 16.67msec and 1667msec, and the voltage that could be maintained was calculated as the voltage holding ratio. The voltage holding ratio was measured using VHR-1 manufactured by Toyo Technica.
[0172] [Table 2]
[0173]
[0174] As shown in the table, PASE obtained by silylation with a silylating agent showed good voltage holding ratio compared with the comparative examples, and in particular, PASE-1 and PASE-2 having a tert-butyl group showed good voltage holding ratio.
[0175] <Evaluation of solubility>
[0176] While 1 g of the liquid crystal aligning agents of Examples 3 to 7 and Comparative Example 1 obtained above were stirred, BCS was dropped respectively, and the solubility was calculated from the weight of the white turbidity by the following formula.
[0177] The evaluation results are shown in the following table.
[0178] Solubility = (BCS amount in liquid crystal alignment agent + BCS amount dropped) / (amount of liquid crystal alignment agent + BCS amount dropped)
[0179] [Table 3]
[0180] Example Polymerization liquid Solubility Example 3 PASE-1 0.680 Example 4 PASE-2 0.143 Example 5 PASE-3 0.065 Example 6 PASE-4 0.060 Example 7 PASE-5 0.075 Comparative Example 1 PAA-1 0.126
[0181] Industrial Applicability
[0182] The liquid crystal alignment film obtained from the liquid crystal alignment agent of the present invention has reliability equal to or higher than that of soluble polyimide, and specifically has high voltage holding ratio characteristics, regardless of whether polyamic acid is used. Therefore, it can be used in a wide range of liquid crystal display elements requiring high display quality.
Claims
1. A liquid crystal aligning agent, comprising at least one of a polyamic acid having a structure of the following formula (1) and a polyimide as an imide thereof, wherein the polyamic acid is a reaction product of a polyamic acid and a silanizing agent, -COOR1(1) In the formula, R1 represents the following formula (1-1): The silanizing agent is at least one selected from the following (S-1) to (S-2), The polyamic acid and the polyimide are obtained by the reaction of a tetracarboxylic acid derivative and a diamine, wherein the tetracarboxylic acid derivative includes a tetracarboxylic dianhydride represented by the following formula (3): X1 is selected from the following formula (X1-8), 2. The liquid crystal alignment agent according to claim 1, wherein The liquid crystal aligning agent contains a polyamic acid having a structure of the formula (1).
3. The liquid crystal alignment agent according to claim 1 or 2, characterized in that: The polyamic acid and the polyimide are obtained by the reaction of a tetracarboxylic acid derivative and a diamine, wherein the diamine is a diamine represented by the following formula (2) or 3,5-diamino-N-(pyridin-3-ylmethyl)benzamide. In formula (2), A1 and A2 are each independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an alkynyl group having 2 to 5 carbon atoms. The structure of Y1 is selected from the following: 4 . A liquid crystal alignment film obtained from the liquid crystal alignment agent according to claim 1 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 4 .
Citation Information
Patent Citations
Liquid crystal aligning agent and liquid crystal display device
JP2001296525A
Photosensitive resin composition and protective film for electronic parts
JP1995319162A
Liquid crystal orientating agent and liquid crystal displaying element
JP2002020754A